МУҲАММАД РИЗО ОГАҲИЙНИНГ “ЗУБДАТ УТ–ТАВОРИХ” АСАРИДА ҚЎЛЛАНГАН ФОРСИЙ СЎЗЛАР ХУСУСИДА (Scientific journal of the Fergana State University, 2023)
The article analyzes some etymological aspects of some Persian words used in the literary work "Zubdat ut- tavorikh" by Muhammad Riza Ogahy and syntactic changes in it.